The Effect of Addition of Ginger Extract and Kencur Extract on the Physicochemical Properties of Instant Temulawak and the Sensory Properties of the Beverage - Aisyah Tri Septiana (Jurnal Gizi dan Pangan Soedirman, 2019)
AbstrACT Temulawak has health benefits, but it is sensationally less favored because it is bitter and has an unpleasant odor, so that in its processing often other spices such as ginger and kencur are added. Temulawak can be processed into temulawak instant drink. This study aims to determine the effect of the concentration of ginger extract (0%, 15%, 30%) and kencur (0%, 15%, 30%) on the physicochemical properties of temulawak instant and sensory brewed drinks. Physicochemical measurements were carried out by analyzing the water content and density of cages of temulawak instant drink. Sensory analysis included color, aroma, spicy taste, sweetness, flavor and likeness. The results showed that the addition of ginger and kencur extract tended to increase water content. The addition of ginger extract and kencur up to 15% increase the flavor and preference of ginger drink. The best combination of the addition of ginger extract and kencur extract was obtained in the treatment of adding ginger extract 15% and the concentration of galingale extract 15% with physicochemical properties of powder drink: water content of 5.20% bb and kamba density of 0.608 g / ml. color 3.24 (brownish yellow); 2.68 spicy flavor (approaching somewhat spicy); sweetness level 3,4 (somewhat sweet); flavor 3.51 (close to tasty); fondness 3.43 (few likes).